Selected Decisions, 15th Edition. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper presents several IMF's selected decisions of the Executive Board and selected documents. The Executive Board approves the draft Guidelines for Determining the Amount of Reserve Assets to Be Paid in Connection with Subscriptions set forth. These guidelines shall be considered by a Committee of the Executive Board established to consider an application for membership in the IMF or to consider a request for an increase in quota that is made outside the framework of a general review of quotas. The amount of the subscription to be paid in reserve assets shall be determined in the light of all the payments of reserve assets made by existing members and the country's external reserve position at the time of membership. Considering the asset payments made by all members in connection with the Sixth General Review of Quotas and adding them to the sum of asset payments taken as the equivalent of 25 per cent of total quotas as of the date of the Second Amendment, the reserve asset payments made by all members average 20 per cent of present quotas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet